Analisis Model UTAUT2 (Unified Theory of Acceptance and Use of Technology) Terhadap Perilaku Penggunaan Layanan Pembelajaran Online Melalui Behavioral Intention - Batu, Reminta Lumban; Hadining, Aulia Fashanah (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2020)
Information and communication technology that is developing rapidly, especially in the world of education, makes online learning easier. E-learning development does not only present online lesson materials but must be communicative and interesting. Online learning must be used to its full potential in order to experience its benefits. Insufficient user behavior can be caused by several factors. UTAUT is one of the latest technology acceptance models. There is a significant influence on the independent hedonic motivation variable on the dependent variable use behavior through the intervening behavioral intention variable. The moderating variable shows that age, gender and experience are not variables that moderate the effect of the independent variable on the dependent variable.